A theoretical framework of the governance institutions of low-income housing in China. (July 2018) - Deng, Feng
This paper develops a theoretical framework for institutional analysis of the governance of low-income housing in the city. I focus on the provision of local public goods as a central issue for low-income housing. Factors that affect the governance structure from the efficiency perspective and the equity perspective, respectively, are explored. I argue that over-subsidisation is an important problem for income-redistribution institutions and, hence, public housing or social housing becomes an important form of governmental intervention in low-income housing. The framework is then applied to low-income housing in China. In particular, I analyse the governance structures of several major types of low-income housing including public rental housing, private low-income housing, work-unit compound and urban village.